2013
DOI: 10.1007/s10815-012-9897-5
|View full text |Cite
|
Sign up to set email alerts
|

Positive association of Apolipoprotein E4 polymorphism with recurrent pregnancy loss in Iranian patients

Abstract: Problem Numerous lines of evidence implicate Apolipoprotein E (Apo E) in lipid metabolism during pregnancy. Hence, a role for its polymorphism has been envisaged in recurrent pregnancy loss (RPL) considering major structural and functional differences between different Apo E genotypes. Method of study A case control study of 81 women with two or more pregnancy losses that did not have any other known risk factors including anatomic anomalies of the reproductive system, infections, immunologic factors, hormonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…While crossing these studies we paid attention to the statistical heterogeneity; if I 2 values were low or moderate (I 2 <50 %), the fixed-effect model was considered for use, otherwise the random-effect model was adopted where the heterogeneity was high among these statistics. In order to assess heterogeneity, we used the I 2 based Q statistic for each genetic contrast to describe the weighted sum of the squared difference and a p-value less than 0.10 was considered in-homogeneous among the included studies [23]. Publication bias was assessed using Begg's unweighted regression test and funnel plots [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While crossing these studies we paid attention to the statistical heterogeneity; if I 2 values were low or moderate (I 2 <50 %), the fixed-effect model was considered for use, otherwise the random-effect model was adopted where the heterogeneity was high among these statistics. In order to assess heterogeneity, we used the I 2 based Q statistic for each genetic contrast to describe the weighted sum of the squared difference and a p-value less than 0.10 was considered in-homogeneous among the included studies [23]. Publication bias was assessed using Begg's unweighted regression test and funnel plots [5].…”
Section: Discussionmentioning
confidence: 99%
“…With thorough evaluation, 431 studies were excluded for inappropriate research, contents that were either not relevant or did not investigate related genes with recurrent pregnancy loss, 16 were retrieved which described the association between the Apo E polymorphism and RPL, and finally, 6 were eligible for meta-analysis [15,17,19,20,23,24]. One of the studies was excluded because the samples were not maternal blood, the tissue used was fetal tissue material [21]; five were excluded because they were presented as a "letter to the editor", meaning that the contents were controversial regarding the association between recurrent pregnancy loss and apolipoprotein E [14,16,[25][26][27]; three were not included because they did not present detailed genotyping information [2,18,28]; and another study was excluded because it concentrated on patients with endometriosis [29].…”
Section: Characteristicsmentioning
confidence: 99%
“…Five publications met the inclusion criteria [8][9][10][11][12]. In Ozdemir et al, the ORs were presented separately for the three different subgroups (i.e., women with a history of RPL, RPL male partners, and RPL patients with no gender restriction) [11].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…APOE has three allelic variants including E2–4. It has been reported that there was a significant higher frequency of allele E4 among a subpopulation of Iranian RPL patients compared with non‐RPL cases (Asgari, Akbari, Zare, & Babamohammadi, ; Poursadegh Zonouzi, Farajzadeh, Bargahi, & Farajzadeh, ). Hypercoagulable state increases the thrombophilia which can be maintained by factors involving in coagulation system and folate metabolism (Blanco‐Molina et al, ).…”
Section: Thrombophiliamentioning
confidence: 99%